Comparison between Mexican and International Medical Graduates’ scores in the ENARM Competing for Clinical Specialities in Mexico during 2012-2019: Data Visualization, Trends and Forecasting Analyses - Mendoza-Aguilar, Alexela-Nerey; Cedillo-Pozo, Aime; Roldan-Valadez, Ernesto (International Journal of Statistics in Medical Research, 2021)
Objectives: Because there is heterogeneity in the ENARM scores obtained between Mexicans and International medical graduates (IMG) in the eight clinical specialities with direct-entry (Anesthesiology, and Emergency Medicine. Geriatrics, Internal Medicine, Medical Genetics, Pediatrics, Pneumology, Psychiatry), we aimed to evaluate those scores. We hypothesized that Mexican test-takers achieve higher scores than IMG with significant growth trends in their exam scores. Methods: This study was cross-sectional, used historical data from the annual public report of the ENARM for eight years (2012 to 2019). We compare the minimum (MinSco) and maximum (MaxSco) scores of each speciality using ANOVA. Mexican versus IMG scores were evaluated with an independent student t-test, trends with Spearman’s correlation coefficient, and a 5-years forecasting trend. Results: There was a significant difference among the MinSco for five surgical specialities; F (7, 115) = 26.611, p = < .001; the global mean of MinSco was 69.133; specialities above this mean were Internal Medicine, Anesthesiology, Pediatrics, and Pneumology. The global mean for MaxSco was 79.422; five specialities were above: Internal Medicine, Pneumology, Geriatrics, Psychiatry, and Medical Genetics. We did not find a significant difference in the MinSco between Mexicans and IMG, but a significant difference was found in the MaxSco between both groups. Conclusions: ENARM represents a market of high-performance test-takers across the clinical specialities. Mexicans and IMG achieved similar entrance scores, but Mexicans showed a higher MaxSco over IMG in all clinical specialities.